A Bridge Planning Simulation with Building Information Model: Steel Frame Structure - Siti Tasyah Dea Fitri Pratama; Andri Irfan Rifai; Ade Jaya Saputra; Joewono Prasetijo (Journal Research of Social Science, Economics, and Management, 2024)
This paper presents a detailed approach to bridge planning and modeling using Building Information Modeling (BIM), focusing on steel frame structures. The implementation of Autodesk Revit Version 2024.1 significantly enhances the precision and efficiency of the planning and modeling process. The methodology involves gathering detailed data references, creating 2D drawings, and developing a comprehensive 3D model for structural analysis and construction design. In the bridge modeling phase, the trusses are constructed using advanced BIM tools, ensuring the structural elements are aligned accurately with the reference framework. This approach facilitates better stakeholder collaboration, improved communication, and more effective resource management. Using BIM technologies and precise data representation in the simulation contributes to better design outcomes, higher accuracy, and improved safety and compliance verification in bridge construction projects. The results demonstrate that integrating BIM in steel frame bridge planning leads to enhanced project efficiency, reduced construction errors, and optimized material use, ultimately supporting long-term sustainability in infrastructure development.